Trans self-identification and the language of neoliberal selfhood: Agency, power, and the limits of monologic discourse - Zimman, Lal (International Journal of the Sociology of Language, 2019)
Sociocultural linguists share with transgender communities a strong interest in the power of individuals to assert agency over linguistic patterns. For trans people, a key principle of activism is gender self-determination, which treats each individual as the ultimate authority on their own gender identity. This article explores some of the ways gender self-determination and self-identification surface in transgender people’s linguistic practices. Three particular manifestations are highlighted: gendered identity labels, third person pronouns, and body part terminology. The observations offered on these subjects are based on a series of ethnographic projects carried out from 2006–2016 in transgender communities across several metropolitan areas in the United States and in online spaces frequented by trans people. However, the analysis goes beyond mere description by treating this kind of individualized linguistic agency as the product of cultural practice rather than an asocial given. Such a perspective introduces questions concerning why this form of agency arose in the time and place that it has. This article frames gender self-identification as an enactment of neoliberal personhood, in which individuals are framed as the driver of their destiny. What the ideology of neoliberal agency obscures, however, is that agency is not an equally distributed resource.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; agentivité; amériques; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; néolibéralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sofia; thématiques; transféminisme; états-unis

Negotiating Parental designations among trans parents' families: An ecological model of Parental identity - Petit M.-P.; Julien D.; Chamberland L. (Psychology of Sexual Orientation and Gender Diversity, 2017)
Parental designations contribute to construct parental identity in the eyes of the child, the parent, and the generalized others. In a hetero/cisnormative context that offers only 2 options for parental identity (male fathers and female mothers), this study (a) provided an overview of the parental designations of trans people and their evolution as parents transitioned, (b) and generated a model of factors associated with the choice of posttransition parental designations. Semistructured interviews guided by the Bronfenbrenner’s ecological model (1988) were administered to 24 Canadian trans parents. The content of the interviews was analyzed using thematic analyses. Results showed that the choice of parental designations was influenced by the timing of childbirth, parents’ consideration of normative strains, negotiation with their children, and issues related to public spaces. Overall, trans parental identity appeared as a multidimensional, multidetermined, nonbinary, and fluid identity in a context of nonalignment between the sex assigned at birth and gender identity. Institutional forms and legislation relative to parenting and birthing must acknowledge the diversity of parental identity and designations.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; identités LGBTQIA2+; maternité; parentalité; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2264; sociologie; thématiques; transféminisme

In a queer time and place: Transgender bodies, subcultural lives - Halberstam, Jack (J.) (New York University Press, 2005)
In a Queer Time and Place opens with a probing analysis of the life and death of Brandon Teena, a young transgender man who was brutally murdered in small-town Nebraska. After looking at mainstream representations of the transgender body as exhibited in the media frenzy surrounding this highly visible case and the Oscar-winning film based on Brandon's story, Boys Don’t Cry, Halberstam turns her attention to the cultural and artistic production of queers themselves. Halberstam examines the “transgender gaze,” as rendered in small art-house films like By Hook or By Crook, as well as figurations of ambiguous embodiment in the art of Del LaGrace Volcano, Jenny Saville, Eva Hesse, Shirin Neshat, and others. Halberstam then exposes the influence of lesbian drag king cultures upon hetero-male comic films, such as Austin Powers and The Full Monty, and, finally, points to dyke subcultures as one site for the development of queer counterpublics and queer temporalities. Considering the sudden visibility of the transgender body in the early twenty-first century against the backdrop of changing conceptions of space and time, In a Queer Time and Place is the first full-length study of transgender representations in art, fiction, film, video, and music. This pioneering book offers both a jumping off point for future analysis of transgenderism and an important new way to understand cultural constructions of time and place.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; cinéma; communication; cours; discipline; fem1000; har4600; identités LGBTQIA2+; lit4700; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme; états-unis; études culturelles

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis